Evolution and control of sexual reproduction in Aspergillus species - Salih, Nadhira Shaban (2016)
Having an understanding of the reproductive mode of an organism is of great importance for gaining insights into the potential for the evolution of a given species, whilst the sexual cycle also provides a valuable tool for strain improvement of species used in industrial applications. About one third of Aspergillus species are reported to be capable of sexual reproduction, but the majority of species are only known to reproduce asexually. However, sexual cycles have recently been discovered in a number of Aspergillus species that were previously thought to be strictly asexual. This has provoked increased research interest both in the possible genetic basis of asexuality and the molecular genetic control of sexual development. The aim of the present study was to investigate the evolution and control of sexual reproduction in Aspergillus species. To achieve this goal, studies were first undertaken to identify novel genes required for sexual development in Aspergillus species. A group of 33 genes was selected, most of which were of unknown function, that had previously been shown to be differentially expressed greater than 10-fold according to whether a MAT1-1 or MAT1-2 gene was resident at the MAT locus of A. oryzae. Homologous genes were identified in the homothallic model species A. nidulans where possible, and then a systematic deletion of these genes were performed in A. nidulans using pyrG marker deletion cassettes. Where transformant strains were obtained these were tested for sexual fertility. A range of phenotypes was observed, from no obvious impact (AN3239 and AN5993), to moderate loss or gain of fertility (AN1356, AN1958, AN4686, AN5791, AN6881, AN7818, AN8184 and AN11253), to complete loss of sexuality (two genes, AN3562 and AN8656). Sexual crossing was then used to restore the deleted genes of interest to confirm by complementation that observed major changes in sexuality were due to the deletion of the target gene. Secondly, the possible roles of high-mobility group domain (HMG) proteins in sexual development of Aspergillus species was investigated. Nine putative high mobility group transcription factor genes were identitfied in A. nidulans by BLAST searching. Three of these had previously been characterized as having prominent roles in sexual development. Systematic deletion of the remaining putative HMG genes revealed that the majority of these also were involved in sexual development. Deletion of one gene (AN3549) resulted in a complete loss of fertility, while deletion of six putative HMG (AN1267, AN1962, AN2755, AN2885, AN4734 and AN5073) resulted in a significant decrease of fertility i.e. they acted as inducers for sex. Deletion of three HMG genes (AN0879, AN3580 and AN10103) had no obvious effect. Finally, investigations were made to determine the potential of sex in some supposedly ‘asexual’ Aspergillus species, some of them being of economic and biotechnological importance. The presence and functionality of mating-type genes and elements of the pheromone signalling pathway were explored. All of the asexual species were found to contain one mating-type gene, consistent with a heterothallic breeding system, and also contained ppgA homologues encoding a pheromone precursor, and preA and preB homologues encoding pheromone receptors. Both the mating-type and pheromone signalling genes were shown to be expressed to mRNA level under conditions favourable for sexual reproduction. These results are of importance as they provide evidence of cryptic sexuality in these species, and the possibility of inducing a sexual cycle in these supposedly asexual species if the correct environmental conditions can be identified. Overall, the identification of several new genes required for sexual reproduction provides significant further insights into the biological control of sexual reproduction in ascomcycete fungi. Indeed, mutation in any of these genes might be the reason for asexuality in several asexual strains; future gene manipulation may lead to induction of sexuality in such asexual species.